If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y-(7-(5y-4))=6
We move all terms to the left:
2y-(7-(5y-4))-(6)=0
We calculate terms in parentheses: -(7-(5y-4)), so:We get rid of parentheses
7-(5y-4)
determiningTheFunctionDomain -(5y-4)+7
We get rid of parentheses
-5y+4+7
We add all the numbers together, and all the variables
-5y+11
Back to the equation:
-(-5y+11)
2y+5y-11-6=0
We add all the numbers together, and all the variables
7y-17=0
We move all terms containing y to the left, all other terms to the right
7y=17
y=17/7
y=2+3/7
| 4.3(1-x)+15x=14.3 | | 10=17-m | | D(D+0D)y=5 | | .-2x-7+3x=10 | | 8y+15–4y=20–13 | | 7=-5(n-4) | | 3*1/5b+5=50 | | 37=8+13+x | | e(4)=16 | | 5x-60+2x=180 | | x+7=x+2 | | 8(x-5)=3(2x+7) | | 4y+17=3y+35 | | 3x-10x=5x+17 | | 3+4x=6+8x+3 | | -108(3.1416)=6(3.1416)(x) | | 3(6+2x)=4(3x+12) | | 36x+18+5=2 | | 17/43=x/301 | | 70/20=n/195 | | y-1+5=2 | | 15x=85/550 | | 20/70=n/195 | | |y-1|+5=2 | | 70/20=195/n | | |a+4|=-1 | | (4x+6)-(3x+1)= | | (1/5)-3b=5 | | 5=t3 | | 5n+65n=37n | | 7y^2=28. | | 6(2-d)=9(-d4) |